53‐2: Development of Cu BCE‐structure IGZO TFT for High‐ppi 85‐in. 8K x 4K 120Hz GOA LCD. Issue 1 (30th May 2018) - Ge, Shi-Min; Li, Shan; Chen, Shu-Jhih; Wang, Xiao; Meng, Yan-Hong; Shi, Wen; Wu, Wei; Zhu, Feng; Wu, Yue; Li, Gong-Tan; Liu, Jing-Jing; Jiang, M; et al.
Abstract : The electrical characteristics of back‐channel‐etched (BCE)‐structure indium‐gallium‐zinc‐oxide (IGZO) thin‐film transistors (TFTs) were studied. Through modifying the passivation layer and optimizing the selection of color‐filter material and the design of the gate‐driver‐on‐array (GOA) TFT structure, the GOA TFTs were made to exhibit good device reliability. Finally, a high‐performance 85‐in. 8K x 4K 120Hz GOA LCD was demonstrated.